2021
DOI: 10.1108/jiabr-01-2019-0011
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the board of directors and the Shariah board on the financial soundness of Islamic banks

Abstract: Purpose The purpose of the study is to examine the relationship between the board of directors (BODs) and the Shariah board (SB) and assess its impact on the financial soundness of Islamic banks (IBs). Design/methodology/approach The authors use a regression model to test the effects of the relationship between the BOD and the SB on the financial soundness of IBs by applying a panel data set of 61 IBs, covering 18 countries from 2008 to 2014. The dependent variable is the Z-score indicator. To test the robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Perhaps this is not surprising as social and moral expectations never come from the centres of power; hence, it applied for Shariah boards. Essentially, this result is similar to the result of Khalil (2021), who found that the Sharia board reduces the financial soundness of Islamic banks.…”
Section: Discussionsupporting
confidence: 88%
“…Perhaps this is not surprising as social and moral expectations never come from the centres of power; hence, it applied for Shariah boards. Essentially, this result is similar to the result of Khalil (2021), who found that the Sharia board reduces the financial soundness of Islamic banks.…”
Section: Discussionsupporting
confidence: 88%
“…If the SSB holds more meetings, SSB coordination can be further improved and sharia-based supervision can be more effective. SSB can also provide regular input to management regarding the distribution of ISR funds or input on ISR disclosures to increase transparency [11]. The formation of SSB is an effort by the government so that Islamic banks can gain trust and convince the public in their function to apply sharia principles consistently.…”
Section: Shariah Supervisory Board (Ssb) Dan Kinerja Keuanganmentioning
confidence: 99%
“…SSB as an independent party that the role of SSB involves providing fatwa, conducting Sharia audits, calculating zakat, and distribution of non-sharia income and guiding the bank in its wider social role [10]. Furthermore, the presence of the SSB can serve as an additional advantage for Islamic banks, as it fosters heightened customer confidence in their banking operations [11].The results of research by Nomran et al, (2020) and Neifar et al, (2020) which reveal that SSB has an effect on the financial performance of Islamic banks is supported by the findings of Alam et al, (2021) in Bangladeshi Islamic banking where SSB can affect financial performance. This is because SSB carries out and functions in monitoring and reviewing banking activities as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Proponents of agency theory suggest that having a high number of independent non-executive directors in the board allows a better activities control and reduces the manager opportunism (Jensen and Meckling, 1976;Fama and Jensen 1983). Moreover, the independent non-executive director support the Shariah Board in order to check the compliance of financial products with shariah principles (Quttainah et al, 2013;Khalil 2021). While, the presence of independent non-executive directors guarantees the independence of the Board of Directors (Amine, 2018;Ramly et al, 2018).…”
Section: Independent Non-executive Directormentioning
confidence: 99%
“…Institutional directors have the expertise and a better knowledge of the of the sector issues compared to other directors (Hakimi et al, 2018;Khalil, 2020). Institutional investors are also more independent to control managers (Jensen, 1993).…”
Section: Institutional Directormentioning
confidence: 99%